STRATEGI MAJELIS ULAMA’ INDONESIA (MUI) GRESIK DALAM MENINGKATKAN PEMAHAMAN ISLAM MODERAT DI RUMAH TAHANAN KELAS IIB GRESIK - Syihabuddin, Muhammad Arif; Muluhah, Malihatul (MIYAH : Jurnal Studi Islam, 2024)
Abstract: This study aims to examine the strategy of the Indonesian Ulama Council (MUI) Gresik in improving the understanding of Moderate Islam in the Detention Center Class II B Gresik. The focus of this research is on the aspects of strategy, process and results. The method uses phenomenological approaches, with observation, interviews, and document analysis. The results Showed that MUI Gresik is through direct and interactive learning, which is framed in Informal Education, in the form of At-Taubah Islamic Boarding School. The program of MUI at the Detention Center Class II B Gresik has 4 programs, namely: Routine activities; Monthly activities; Annual activities; Incidental activities. By using strategies directly, interactively, empirically and independently; The increase in understanding and intellectual ability of residents, cognitive strategies, verbal information, as well as motoric skills and affective attitudes, both in the fields of the Qur'an, Akidah, Fiqh and Counseling Guidance. Keywords: Moderate Islam, Indonesian Ulama Council, Detention Center